Raport z akcji prozdrowotnej Pracodawca dbający o zdrowie pracowników – ocena zaangażowania pracodawców - Kukawska, Katarzyna (Studia Prawa Publicznego, 2022)
Employers’ occupational health initiatives can be divided into two categories: tasks speciﬁed in the acts of activity, and non-obligatory activities. Workplace health pro-motion entails shaping the health behaviour of employees, the physical conditions of the work environment and improving employees’ access to medical services. Supra-compulsory actions in the ﬁeld of employee health protection can be referred to as pro-health activities. The pro-health campaign An employer who cares about employees’ health was carried out by the Heliodor Swiecicki Clinical Hospital in Poznan. In the years 2019-2020, screening tests for the early detection of head and neck cancers were performed in cooperation with Wielkopolska companies. The aim here is to analyse the proﬁles of employers engaging in pro-health campaigns in terms of the size, number of employees and the industry. The study assessed the effectiveness of the health campaign by means of the percentage of employees qualiﬁed for the study and the percentage of employees referred to the Clinical Hospital for further diagnostics. 14 employers participated in the research. In the sales sector, 7 large and 2 me-dium-sized enterprises from the industrial sector, 2 medium-sized enterprises and 1 public sector company, as well as 2 large enterprises from the transport sector. A total of 2,428 employees were declared for the study, 710 people were qualiﬁed for the study, and 447 employees were required to undergo in-depth diagnostics. Large enterprises employing more than 250 people were more willing to participate in the pro-health campaign, although they had a lower percentage of employees qualiﬁed for the research compared to medium-sized or small enterprises.